Growth of Virulent and Avirulent Mycobacterium tuberculosis Strains in Human Macrophages - Zhang, Ming (American Society for Microbiology, 1998)
Mycobacterium tuberculosis H37Rv causes progressive disease in animals, whereas the H37Ra strain does not. The relevance of this difference in virulence to human infection is uncertain because these strains have been shown to have similar growth rates in human macrophages. To evaluate the intracellular growth of M. tuberculosis strains in macrophages under conditions similar to those encountered in vivo, we infected human monocyte-derived macrophages with H37Ra, H37Rv, or one of four isolates from tuberculosis patients at a low bacillus-to-macrophage ratio. H37Rv and the patient isolates grew significantly faster than H37Ra, based on the numbers of CFU and acid-fast bacilli. These findings did not result from extracellular mycobacterial growth, differential macrophage viability, or bacillary clumping. In contrast to other published results, these findings indicate that the virulence characteristics of M. tuberculosis strains in animal models are relevant to human tuberculosis infection.